2010
DOI: 10.1103/revmodphys.82.2099
|View full text |Cite
|
Sign up to set email alerts
|

Normalization and global analysis of perturbations of the hydrogen atom

Abstract: The hydrogen atom perturbed by sufficiently small homogeneous static electric and magnetic fields of arbitrary mutual alignment is a specific perturbation of the Kepler system with three degrees of freedom and three parameters. Normalization of the Keplerian symmetry reveals that the parameter space is stratified into resonant zones of systems, each zone with an internal dynamical stratification of its own ͑Efstathiou, Sadovskií, and Zhilinskií, 2007, Proc. R. Soc. London, Ser. A 463, 1771͒. Based on the fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 230 publications
(104 reference statements)
2
49
0
Order By: Relevance
“…[10], see also Ref. [11]). Finally Section IV is devoted to a very different approach, in which the quantum Hamiltonian is solved directly using the Bethe ansatz.…”
Section: Introductionmentioning
confidence: 99%
“…[10], see also Ref. [11]). Finally Section IV is devoted to a very different approach, in which the quantum Hamiltonian is solved directly using the Bethe ansatz.…”
Section: Introductionmentioning
confidence: 99%
“…This role is similar to the one played by the separatrix in purely one-dimensional systems [30]. We remark that the existence of these singular structures had been essentially ignored in the physics literature until their recent introduction in the domain of atomic and molecular systems [29,31,32]. The aim of the present article is to render these new mathematical tools accessible to a broad audience in the context of nonlinear optics.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that the variables x 0 ;x 1 ;x 2 ;x 3 constitute a basis for the set of polynomial functions commuting with K [29]. In particular, since fH;Kg 0, one can write the Hamiltonian as…”
Section: Construction Of the Singular Torimentioning
confidence: 99%
See 2 more Smart Citations